The Prospect of Antitrust Law and Policy in the Twenty-First Century: In Reference to the Japanese Antimonopoly Law and Japan Fair Trade Commission - Toshiaki Takigawa (Washington University Global Studies Law Review, 2002)
In this Article, I examine Japanese competition law and policy with a view toward increasing its effectiveness in establishing a pro-competitive Japanese economy.
Keywords: Japan; Antitrust law; Japan Fair Trade Commission; Competition (Economics)